واقع استخدام شبکة التواصل الاجتماعى الفیسبوک فى الأرشیفات الوطنیة العربیة والأجنبیة : دراسة تحلیلیة مقارنة - د. تفیدة سمیر محمود (المجلة الدولية لعلوم المكتبات والمعلومات)
This research deals with the reality of use of the social network (facebook) in the national archives of Arab and Foreign comparative analysis.With the beginning of the third millennium, national archives have movedtowards second generation web2 application to reach users and connect with thegrowing generation of web 2 users, increase free access to archives collectionThis study aims to limit the national Arab archives that have pages on thesocial networking site face book ,and the description and analysis of the pages ofthe Arab archives on the social networking site Facebook, and a comparativestudy between the pages of Arab and Foreign national archives on face book interms of the modernity of information provided to beneficiaries and the extent ofcomprehensiveness and adequacy. The study found that the existence of Arabarchives on internet is almost weak, and that some Arab archives do not use themeans of social communication in general due to lack of financial and humanresources and legal risks and security risks.The foreign archives update their face book pages almost daily ,whichmakes it logical to users to visit these pages on a regular basis ,and thecontinuity and updating of the update shows the importance given by the nationalarchives of its presence on face book unlike Arabic archives.The study also found that the Arab archives method is linked to web 1,and that the presence of Arab archives on the social networking site face book isan important presence of existence only on face book and does not reflect thehistorical value found in the Arab national archives.